The method of expert evaluation of specific abilities to practice judo - proposition of Japanese top level university judo coaches - Maekawa, N.; Hirose, N.; Ito, K.; Ishii, K.; Koshino, T.; Yazaki, R.; Tamura, R. (Archives of Budo, 2013)
This study`s aim was a rating scale that assists managers in determining judo practitioners` abilities absent information derived from competition outcomes. This was carried out by gathering and analyzing factors considered important by judo coaches when evaluating such abilities. Material and Methods: Investigation I: seven judo experts, all currently active in judo instruction and ranked 4th dan or greater by the Kodokan Judo Institute of Japan, conferred to produce a list of 20 markers that indicate how an individual will perform in competition. Each item was rated with a score from between 1 (least important) and 10 (most important) by the 48 judo coaches that were to participate in the 2011 Japan Nationwide University Weight Categorized Judo Championships. Investigation II: the criteria assembled in Investigation I were applied to a university intramural judo tournament to assess their validity and reliability. Results: Eleven of the criteria identified in Investigation I were eliminated, narrowing the rating scale factors to the following nine items: general motor ability, mental toughness, attention to form, stamina, tactics, assertiveness of the athlete in applying kumi-te, proper kumi-te style, standing defense, and mat skills. High correlation coefficients between the predicted and actual competition rank, predicted competition rank and rank derived from the rating form, and actual competition rank and rank derived from the rating form were confirmed (r = 0.807, 0.821 and 0.705, respectively, p < 0.001 for all; Spearman`s Rank Test). Conclusions: The nine rating items selected in this study met specified standards of validity and reliability. The results suggested that the approaches taken by judo coaches in assessing practitioners` ability are appropriate and contribute to the quality of judo not only in Japan.